Immunogenicity and safety of the non-typable Haemophilus influenzae–Moraxella catarrhalis (NTHi-Mcat) vaccine administered following the recombinant zoster vaccine versus administration alone: Results from a randomized, phase 2a, non-inferiority trial - Ilaria Galgani; Airi Põder; Rain Jõgi; Veli-Jukka Anttila; Stefano Milleri; Alberto M. Borobia; Odile Launay; Marco Testa; Daniela Casula; Luca Grassano; Annaelisa Tasciotti; Marie Dozot; et al. (Human Vaccines & Immunotherapeutics, 2023)
A candidate AS01-adjuvanted vaccine containing four surface proteins from non-typable Haemophilus influenzae and Moraxella catarrhalis (NTHi-Mcat) has been developed to help prevent exacerbations of chronic obstructive pulmonary disease (COPD). Sequential administration of different vaccines containing the same AS01-adjuvant system could lead to immune interference. We compared administration of NTHi-Mcat following AS01-adjuvanted recombinant zoster vaccine (RZV) versus NTHi-Mcat alone. This phase 2a, open-label trial (NCT03894969) randomized healthy current or former smokers (50–80 years) without COPD to administration of NTHi-Mcat at 1, 3 or 6 months after RZV or to NTHi-Mcat alone (2-dose for both vaccines). Primary outcome was non-inferiority of the humoral immune response to NTHi-Mcat administered 1 month after RZV versus NTHi-Mcat alone, evaluated by specific antibody geometric mean concentration (GMC) ratio with 95% confidence intervals (CIs). The per-protocol set included 411 participants. Primary objective was met; lower limit of the 95%CI for the GMC ratio above 0.667 for all four vaccine antigens, 1 month after the second NTHi-Mcat dose. NTHi-Mcat induced similar immune response regardless of whether administered alone or 1, 3 or 6 months following RZV. Safety and reactogenicity profiles were acceptable; adverse event frequency was similar among study groups. Injection site pain was the most common symptom. No new safety concerns were identified. The study demonstrated non-inferiority of the immune response elicited by NTHi-Mcat administered sequentially to RZV versus NTHi-Mcat alone, indicating no immune interference. Starting from 1 month, no specific interval is required between RZV and NTHi-Mcat containing the same AS01-adjuvant system components in different quantities.